School Board Policies on Prevention and Management of Anaphylaxis in İstanbul: Where Do We Stand? - (:unkn) unknown (My University, 2016)
0

Background: Allergic diseases with a potential for anaphy-laxis pose a critical public health issue in schools. Aims: This study was carried out to identify the current sta-tus of prevention and management of anaphylaxis in school children with the main goal of establishing such an action plan.Study Design: Cross-sectional study.Methods: Schools were randomly selected from 11 differ-ent regions of Istanbul. A questionnaire was filled out by 2596 teachers/school principals from 232 public schools. Results: A school safety committee was absent in 80% of elementary schools (ES) and 60.8% of preschools (PS). Al-though some form of health recording system was available in many schools, no such system was available in 24.5% of ESs and 10% of PSs. A specific inquiry for detecting chil-dren with food allergies was a routine practice in only 4% of ES and 10% of PS. Approximately 27% of teachers stated that monitoring children in school places was not possible at all times. Eighty four percent stated that no written anaphy-laxis treatment protocol was available in their school and only around 2.3% in ES and 3.1% in PS stated that they would perform an epinephrine injection in the event of ana-phylaxis. Conclusion: Our survey demonstrated critical gaps in the organization of schools for the management of children at risk of anaphylaxis. Data derived from this study would provide the initiative for legislators to review the current situation of school health policies along with the relevant authorities to establish school anaphylaxis guidelines
Keywords: Cerrahi